The associations between maternal lifestyles and antenatal stress and anxiety in Chinese pregnant women: A cross-sectional study - Qingzhi Hou (Nature Portfolio, 2018)
Abstract The study aimed to investigate the associations between maternal lifestyles and antenatal stress and anxiety. 1491 pregnant women were drawn from the Guangxi birth cohort study (GBCS). A base line questionnaire was used to collect demographic information and maternal lifestyles. The Pregnancy Stress Rating Scale (PSRS) and Self-Rating Anxiety Scale (SAS) were used to assess prenatal stress and anxiety, respectively. Regression analyses identified the relationship between maternal lifestyles and prenatal stress and anxiety: (1) Hours of phone use per day was positively correlated to prenatal stress and anxiety and increased with stress and anxiety levels (all P trend < 0.05). In addition, not having baby at home was positively correlated to prenatal stress. (2) Self-reported sleep quality was negative with prenatal stress and anxiety, and decreased with stress and anxiety levels (all P trend < 0.01). Moreover, not frequent cooking was negatively correlated to prenatal stress and having pets was negatively correlated to prenatal anxiety (P < 0.05). However, having pets was not correlated to prenatal stress (P > 0.05). Our results showed that adverse lifestyles increase the risk of antenatal stress and anxiety, a regular routine and a variety of enjoyable activities decreases the risk of prenatal stress and anxiety.